Procurement in the field of military property: to the activities of the Russian Supply Committee in America in 1917 - V. M. Tarelko (Омский научный вестник: Серия "Общество. История. Современность")
In the article has been attempted to consider the position of the Russian Supply Committee in America, the problems and the state of its structural units during the significant 1917 year of last active cooperation with the Allied powers in military procurement during the First World War. As the Russian Supply Committee is currently presented fragmentally in the scientific historical literature, the author has identified the following purpose of this article — to reduce and expand the available material on the activities of the Russian Supply Committee into a unified picture, paying special attention to the perception of its activities in the American press, the problem of transportation, the issue of the introduction of liquidation policy in relation to purchase order, efforts to purchase transport property. The article is written on the basis of unpublished sources (materials of the office work of the Russian Supply Committee, correspondence of General N. M. Khrabrov with the Main Directorate for Foreign Supply and the authorized Ambassador from the Russian government B. A. Bakhmetyev, orders and instructions of the Main Directorate for Foreign Supply, materials of the Special Investigative Commission) identified in the funds of the Russian State Historical Archive. As a result, the author concluded that in the conditions of political instability and stagnant organizational and structural problems, the Russian Supply Committee could not properly resolve the issue of purchasing military property on the American market.